Analisis Pengaruh Voucer Promo Terhadap Keputusan Pembelian Pada Layanan Online Food Delivery Di Kalangan Mahasiswa Kota Bandung - Irfan Azhar Pratama (International Journal Administration, Business & Organization, 2023)
The purpose of this study is to find the effect of promo vouchers on purchasing decisions on online food delivery services among Bandung City students. This research uses quantitative descriptive research. The data collection technique used a questionnaire with a total of 102 respondents. The analytical method used is simple linear regression analysis which aims to find the effect of variable x (promo vouchers) on variable y (purchasing decisions). The results of the analysis from each table are that the variable x (promo voucher) has an influence on the variable y (purchasing decision) of 57.4%.